Motivation as a Catalyst for Employee's Productivity in Delta State Ministry of Health, Asaba Nigeria. (Lapai Journal of Economics, 2022)
Motivation has become a source of increased output in recent times in the workplace. The main aim of this study is to examine motivational factors affecting the employees’ productivity in Delta State Ministry of Health, Asaba-Nigeria. This study employed a cross-sectional data with a sample of 234 respondents from ministry of health Asaba, concerning their high level of productivity which was achieved through motivation from Government in terms of better salary and regular promotions. The result from the Chi-Square analysis indicates that motivation through increased special salary payment and regular promotions from the state government, do enhance productivity. It was therefore recommended that state Government must continue in that fashion so that such high level of success would maintained.